Biofortification Prioritization Index (BPI) - HarvestPlus (International Food Policy Research Institute, 2013)
The Biofortification Prioritization Index (BPI) ranks countries according to their potential for introducing nutrient-rich staple food crops to fight micronutrient deficiencies, also known as hidden hunger. The BPI focuses on the three key micronutrients (vitamin A, iron, and zinc) that the World Health Organization deems among the most limiting in diets. Lack of these and other micronutrients impairs cognitive and physical development and increases vulnerability to infectious diseases, especially among children and women.